Vitamin D3 induces stem cell activation via Lgr5-Bmi1 expression and improving mouse colitis histology index - Wibowo, Satrio; Pramadhani, Almira; Subandiyah, Krisni; Handono, Kusworini; Poeranto, Sri (Narra Sains Indonesia, 2023)
Conventional therapy for inflammatory bowel disease using long-term anti-inflammatory drugs does not seem to provide optimal results. Adjuvant therapy using vitamin D3 is believed to have an essential role in repairing the colonic mucosa through the activation of colonic stem cells. The aim of this study was to demonstrate the effect of vitamin D3 in mucosal repair through stem cell activation, marked by leucin-rich repeat-containing G protein-coupled receptor 5 (Lgr5) and B lymphoma Mo-MLV insertion region 1 (Bmi1) expression and decrease the mouse colitis histology index (MCHI) score. In this study, 50 Mus musculus strain BALB/c were divided into five groups: negative control group, colitis group, and colitis groups with vitamin D3 administration of 0.2 mcg, 0.4 mcg, and 0.6 mcg per 25 g body weight for seven days. Dextran sulfate sodium (DSS) 5% was used to induce colitis. Lgr5-Bmi1 expression was measured using immunodoublestain fluorescent labeling method. Our data suggested that administration of vitamin D3 significantly increased expression of Lgr5-Bmi1 in the colonic mucosa. The colitis group treated with the highest dose of vitamin D3 (0.6 mcg/25 gram) showed the lowest MCHI score (3.60±0.64) while the lowest dose of vitamin D3 had the highest MCHI score (12.60±1.47). In conclusion, stimulating stem cells, vitamin D3 administration stimulates mucosal regeneration, as demonstrated by upregulated expression of Lgr5-Bmi-1.